Community advisory committee as a facilitator of health and wellbeing: A qualitative study in informal settlements in Nairobi, Kenya - Chumo, Ivy; Kabaria, Caroline; Oduor, Clement; Amondi, Christine; Njeri, Ann; Mberu, Blessing (Frontiers in Public Health, 2023)
Introduction A range of community engagement initiatives to advance health and wellbeing are currently taking place in informal settlements in low and middle income countries (LMICs), including community and stakeholder meetings, use of radio, film, TV programs and other information, education and communication materials (IECs) organized by different stakeholders. While these initiatives tend to focus on unidirectional flow of information to communities, the need to incorporate initiatives focusing on bi or multi-directional flow of information have been identified. Despite the extensive body of literature on community engagement, the role of Community Advisory Committees (CACs) in advancing health and wellbeing in informal settlements is still a puzzle, occasioned by considerable ambiguity. A community advisory committee is a dedicated group of volunteers to support health and wellbeing needs of their community using a community approach. Researchers and project implementers work in partnership with CACs to successfully implement their activities within the target community. Methods In this paper, using in-depth interviews, we document the roles of CACs in advancing health and wellbeing in Korogocho and Viwandani informal settlements in Nairobi, Kenya. Results Study participants described the role of CAC in advancing health and wellbeing through education and awareness creation, advisory roles in research and implementation goals, protecting community interests and acting as gatekeepers and collaborators to community partners. Identified barriers to achieving CAC roles include lack of finance and other field resources, being labeled as organization staff and low involvement by some upcoming and emerging local leaders on issues which involve the CAC constituents. Enablers of CACs in their roles include possession of appropriate skills and values by members; involvement of the community in the selection of members, regular consultative and advisory meetings, representativeness in the composition of CAC membership and knowledge about the community. Conclusion We conclude that CACs play key roles in advancing health and wellbeing in informal settlements and that existing CACs mechanisms and operations need to be given due consideration by researchers, project implementers and local authorities right from project conceptualization. CACs need recognition beyond consultations and placations during research and project implementation to a veritable social structure for community's social viability and survival as well as partners in development for inclusive urbanization process. While CACs have contributed in advancing health and wellbeing in informal settlements, there is need for a long-term strategy to optimize their impact and reduce puzzles around their roles.